Ethics & Governance of Research: Focus on Research Ethics Committees globally, disparities across regions and the understanding of the structures and systems in place for publicly available information - Tzermpinou, Anthi (Bioethica, 2023)
This publication presents the findings of the Research submitted for the degree of MRes in Bioeconomy Biotechnology & Law that was conducted in May 2022 at the International Hellenic university in Thessaloniki, Greece. The original research purpose was to gather information on the coherence or disparities that exist in the current environment within the established ethics committees on the country or regional level. Several elements were taken into consideration on their structural systems in place in terms of: governance, standard operating procedures, trainings, and reporting systems (internal but as well as external)] but the outcome of this research serves also as a baseline as “the outcome of a person’s understanding (author) on the current environment based on publicly available information” to reach to the desired result which is to establish a clear understanding on the current procedures of the ethics committees from a person without extensive knowledge or constant exposure to their inner environment. Therefore, there are two elements that were simultaneously under research. This article presents the results based on the findings of this research but as well the barriers (limitations and restraints) contributing to their understanding. The author provides closing recommendations on the organizational level but as well on a fundamental level to provide alignment but as well as a request for clarity on the existing publicly available information in a manner that is easy to understand to the simple reader which contributes to transparency on research.